Trade and environment at the WTO (WTO GenevaCH, 2004)
Presents a brief history of the trade and environment debate. Deals with the Doha mandate on trade and environment; market and environmental requirements; the effects of trade liberalization on the environment; and, the relationship between MEAs and the WTO. Looks at transparency and relations with other organisations and relevant GATT/WTO provisions. Presents an overview of environment-related disputes.
Keywords: TRADE